2021
DOI: 10.1007/s00018-021-03970-z
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin2 protects against lethal sepsis by suppressing the pyroptosis of dendritic cells

Abstract: Sepsis is defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. Sestrin2 (SESN2), a highly evolutionarily conserved protein, is critically involved in the cellular response to various stresses and has been confirmed to maintain the homeostasis of the internal environment. However, the potential effects of SESN2 in regulating dendritic cells (DCs) pyroptosis in the context of sepsis and the related mechanisms are poorly characterized. In this study, we found that SES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…It was hypothesized that the increase in the number of intestinal macrophages and dendritic cells at 1–3 h could be related to the activation of pancreatic enzymes in pancreatic cells, which led to a large number of immune cells activated and chemoattracted to the intestine, further activating the intestinal innate immune cells, and ultimately resulting in an enhanced inflammatory response. However, the number of intestinal macrophages and dendritic cells was decreased at 6–72 h, when the intestinal innate cells could trigger pyroptosis, causing a more intense inflammatory cascade with massive death of immune cells ( 57 ). After 120 h, the number of intestinal macrophages and dendritic cells gradually returned to normal levels, and the SAP rats were in a self-healing state.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that the increase in the number of intestinal macrophages and dendritic cells at 1–3 h could be related to the activation of pancreatic enzymes in pancreatic cells, which led to a large number of immune cells activated and chemoattracted to the intestine, further activating the intestinal innate immune cells, and ultimately resulting in an enhanced inflammatory response. However, the number of intestinal macrophages and dendritic cells was decreased at 6–72 h, when the intestinal innate cells could trigger pyroptosis, causing a more intense inflammatory cascade with massive death of immune cells ( 57 ). After 120 h, the number of intestinal macrophages and dendritic cells gradually returned to normal levels, and the SAP rats were in a self-healing state.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed the pyroptosis of peripheral immune cells in patients in septic shock ( 91 , 92 ). Recently, we observed pyroptosis of splenic dendritic cells (DCs) in CLP-induced septic mice ( 93 ). Similarly, Xu et al noticed the pyroptosis of neural cells in septic mice and found that the inhibition of pyroptosis could alleviate brain damage and cognitive impairment in SAE.…”
Section: The Immune Response Of Cns In the Development Of Saementioning
confidence: 99%
“…Previous studies have indicated that depletion of DCs seriously affects the prognosis of sepsis, which was regarded as a vital target for sepsis treatment. 5,6 Sepsis associated hyperinflammation allows accumulation of damage-associated molecular patterns (DAMPs) in peripheral circulation, including high mobility group protein-1 (HMGB1), 7 histones, mitochondrial DNA (mtDNA), and so forth. 8 DAMPs serve as potent activators of the immune system in initiating and perpetuating non-infectious inflammation to induce systemic inflammation, leading to organ injury and paralysis of immune cells, 9,10 thus resulting in poor prognosis of sepsis.…”
Section: Susceptibility To Opportunistic Pathogens Increases Signific...mentioning
confidence: 99%
“…As the most important antigen presenting cell, DCs play an essential role in bridging innate and adaptive immunity, participating in maintaining immune homeostasis. Previous studies have indicated that depletion of DCs seriously affects the prognosis of sepsis, which was regarded as a vital target for sepsis treatment 5,6 . Sepsis associated hyperinflammation allows accumulation of damage‐associated molecular patterns (DAMPs) in peripheral circulation, including high mobility group protein‐1 (HMGB1), 7 histones, mitochondrial DNA (mtDNA), and so forth 8 .…”
Section: Introductionmentioning
confidence: 99%